GAMBARAN PERILAKU MENGKONSUMSI ALKOHOL (TUAK) TERHADAP KEKEBALAN TUBUH (IMUNITAS) PADA MASYARAKAT DI DESA KAMPUNG TENGAH PANCUR BATU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Suci Wahyuni (Jurnal Kesehatan, 2023)
Tuak is a traditional alcoholic drink in North Sumatra, especially in the Toba Batak tribe, which contains 4% alcohol. Tuak is made from coconut or palm stems and the water is taken and then mixed with rari. Drinking palm wine is part of a tradition that has been passed down from generation to generation in Kampung Tengah Pancur Batu Village, Deli Serdang Regency, North Sumatra Province and is very difficult to get rid of in people's habits. Even though alcohol can have a serious impact on health, namely drunkenness, weight gain, high blood pressure, decreased immune system, cancer, heart disease, respiratory problems and liver disorders. The aim of the study was to describe the behavior of consuming alcohol (tuak) on immunity in the people of Kampung Tengah Pancur Batu Village, Deli Serdang Regency, North Sumatra Province. This type of research is qualitative research with a case study method. This research was carried out on the behavior of consuming alcohol (tuak) on immunity (immunity) in the community in Kampung Tengah Pancur Batu Village, Deli Serdang Regency, North Sumatra Province by collecting data from key informants and supporting informants. The habit of drinking palm wine in the community, the behavior of consuming alcohol (tuak) on immunity (immunity) in the community in Kampung Tengah Pancur Batu Village, Deli Serdang Regency, North Sumatra Province is included in the heavy category and there is a relationship between perceptions of health and the habit of consuming palm wine in Kampung Tengah Pancur Village. Batu Deli Serdang Regency, North Sumatra Province.